Sharī’ah and the Politics of Pluralism in Indonesia - Lukito, Ratno (Studia Islamika, 2007)
Keeping in mind the Indonesian Government's policy regarding legal pluralism, this article will take a closer look at how the Government deals with the existence of both Islamic law and customary law (adat). The adoption of "state law pluralism", especially by the New Order regime since 1970s, has had an evident impact on the way the state handles the institution of adat and Islamic law (shari'ah). The question is what is the motive behind employing this strategy? This is a question that necessitates more a socio-political approach in the study of comparative law, drawing on a number of regulations and acts related to adat and Islamic law as the primary sources.DOI: 10.15408/sdi.v14i2.545